Safety system for railings / Syaima Mohd Fauzi and Ezzat Fahmi Ahmad - Mohd Fauzi, Syaima; Ahmad, Ezzat Fahmi (2023)
Building safety has been established as a requirement to lower the likelihood of accidents occurring onsite. One of the crucial components in building safety are railings that can prevent falls or accidents from elevated positions. There have been numerous incidents documented throughout the years of railings collapsing because people leaning on them and overloading them, resulting in the loss of many lives. People must be conscious of their surroundings and understand that not all architectural structures are as sturdy as they appear to be. The aim of the study is to improve people’s safety at high-rise buildings through an innovative safety system for railings. This study compiles the approaches employed in previous studies in the effort to create a new safety system for railings in high-rise buildings in Malaysia. Simple components such as steel plates, springs, an alarm, and electric circuit are in the creation of this safety system. The system is mostly beneficial for buildings occupied by a large number of people at a time like schools or malls. Using innovation framework as a methodology, the research process workability could be determined. the framework is a composition of four main elements: ideation, selection, development, and commercialisation